Anion-specific aggregation induced phosphorescence emission (AIPE) in an ionic iridium complex in aqueous media. Issue 95 (6th October 2015) - Li, Guangfu; Guan, Wei; Du, Shuang; Zhu, Dongxia; Shan, Guogang; Zhu, Xiaojuan; Yan, Likai; Su, Zhongmin; Bryce, Martin R.; Monkman, Andrew P.
Abstract : Efficient aggregation-induced-phosphorescent-emission (AIPE) of an ionic Ir(iii ) complex occurs when the counterion (PF6 − ) is exchanged specifically by ClO4 − in aqueous media. As a result, a rapid, highly selective "turn-on" phosphorescent response to ClO4 − is observed in aqueous media. Abstract : Efficient aggregation induced phosphorescence emission (AIPE) of an ionic Ir(iii ) complex occurs when the counterion (PF6 − ) is exchanged specifically by ClO4 − in aqueous media. As a result, a rapid, highly selective "turn-on" phosphorescent response to ClO4 − is observed in aqueous media. These studies pave the way for a new efficient phosphorescence-based detection strategy for anions.